Bio Prospecting In Nigeria: Evaluating The Adequacy Of Laws And Practices And The Implications For The Environment - Ohuruogu, Chris Chijioke; Okoye-Asoh, Chukwudumebi (Journal of Sustainable Development Law and Policy, 2025)
Bio-prospecting is a subject of interest especially as to its utility in environmental protection. It is the purposeful evaluation of wild biological materials in search of valuable new products and involves the application of advanced technologies to develop new pharmaceuticals, agrochemicals, cosmetics, flavorings, fragrance, industrial-enzymes and other products from biodiversity. On the face of it, bio-prospecting is a major threat to the continuous flow of genetic resources. However when substituted with other consumption patterns or when properly regulated such that benefits derived from it are invested in technologies geared towards conserving the databank of the bio resources, or the provision of the needs of the local peoples whose practices mount undue pressure on the resources, it becomes a viable tool for resource conservation. This paper examines the regulatory regime of bio-prospecting in Nigeria from international and national perspectives to evaluate their adequacy. It also examines the environmental implications of the state of affairs and recommends the protection of the local peoples’ interest, and their involvement in strategic planning and policy formulation on bio prospecting, amongst others as a way of bio conservation to profit bio-prospecting.